The Wind Loading Characteristics of MAN Type Dry Gas Storage Tank - Xinpeng Liu; Zhitao Yan; Zhengliang Li; Junfan Chen; Jingbo Liu (Advances in Civil Engineering)
The effects of Reynolds number (Re) and surface roughness on the wind pressure coefficient on a MAN type dry gas tank were analyzed in detail by wind tunnel tests. A wind load calculation model was then established, which is suitable for the wind resistant design of the gas tanks. The test results revealed that in the range of 7 × 105 < Re < 1.0 × 106 (supercritical regimes), the drag coefficient (Cd) and wind pressure coefficient remained constant, consistent with 2D cylinders in a uniform flow. However, in common with 2D cylinder flows, the surface roughness with the spacing ratio (λ) greater than 0.9 had a significant effect on the wind pressures coefficient. The minimum pressure coefficient (Cpmin) sharply increased from −2.3 to −0.65 with increasing surface roughness. The corresponding angle for the minimum pressure coefficient θmin was in between 140°and 90°, which was in a gradual decreasing trend with the increase in surface roughness of the model. The calculation method of the wind pressure coefficient with vary surface roughness was proposed, based on which, the calculation results were in good agreement with the test data.